Bureaucratic Reform in Public Service: Strengthening the Apparatus - Dede Saidah (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The results of the research show that the arrangement of Task and Function of thePopulation Service Institution in charge of and responsibility of providing populationadministration services in Jatinangor sub-district has been in accordance with itsduties and functions based on Local Regulation No. 11 of 2016. Structuring humanresources apparatus has been implemented in the hope that the human resourcesapparatus to be better in carrying out the task of service to the community. As for thecompetence of tbsp apparatus is better so as for the administration of populationadministration to be better. While the commitment to strengthening the performanceaccountability of the apparatus has succeeded in realizing quality service, so that theadministrative services of population become better.